Ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane as well as preparation method and application thereof
By covalently grafting the hexagonal boron nitride composite proton exchange membrane of ionic liquid, the shortcomings of the existing thin proton exchange membrane in terms of mechanical strength, gas permeability and oxidation resistance are solved, and the comprehensive improvement of proton conductivity, mechanical strength, oxidation resistance and thermal stability are achieved.
Patent Information
- Application Number
- CN202411809696.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The existing thin proton exchange membranes have shortcomings in mechanical strength, gas permeability and oxidation resistance stability, and it is difficult to improve proton conductivity and stability at the same time.
The hexagonal boron nitride composite proton exchange membrane is adopted for covalent grafting of ionic liquid and hexagonal boron nitride. The mechanical properties and proton conductivity of the membrane are improved while enhancing the antioxidant and thermal stability.
The proton conductivity, mechanical strength, oxidation resistance and thermal stability of the proton exchange membrane are achieved, and the problems of easy loss of single ion liquid doping and easy precipitation of single hexagonal boron nitride doping are solved.
Smart Images

Figure CN119650776A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water using a proton exchange membrane, and in particular to an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is one of the most ideal energy carriers and clean energy providers in the world, and is known as the ultimate energy source of the 21st century. Green hydrogen will become the inevitable direction of the development of the hydrogen energy industry. At present, water electrolysis is the main method of hydrogen production. Compared with alkaline water electrolysis and solid oxide water electrolysis, proton exchange membrane water electrolysis (PEMWE) hydrogen production technology has zero carbon pollution emissions, and the hydrogen production system can be shut down at any time. It is more suitable for renewable green electricity hydrogen production such as wind power generation and photovoltaic power generation. It is considered to be a water electrolysis hydrogen production technology with excellent development prospects and good application prospects.
[0003] As a key component of PEMWE components, proton exchange membrane (PEM) has two main functions: one is to ensure H + The first is to prevent the crossover of H2 and O2 from the anode to the cathode, and the second is to prevent the crossover of H2 and O2 on both sides of the anode and cathode. Therefore, the PEM used for PEMWE needs to have high proton conductivity, low gas permeability, and excellent mechanical properties and stability. When the membrane thickness is greater than 100μm, the membrane surface resistance (>100mΩ / cm2) has problems of low proton conductivity and high cost. In view of the above points, reducing the membrane thickness is the future development direction of PEM for water electrolysis. Although reducing the membrane thickness will reduce the internal resistance of the electrolytic cell and improve the proton conductivity, as the membrane thickness decreases, the gas permeability will increase, the mechanical strength will decrease, and it will be more susceptible to mechanical, chemical and thermal degradation. Therefore, the optimization and improvement of thin PEM is the key to current research.
[0004] In the process of optimizing PEM, the performance of PEM can be improved by introducing specific ionic liquids (ILs), heteropolyacids, etc. to improve the proton conductivity of the composite membrane and introducing inorganic fillers such as hexagonal boron nitride (hBN) to reduce the gas crossover and stability of PEM. Hexagonal boron nitride (hBN) is a two-dimensional (2D) nanomaterial that is similar to graphene oxide (GO) in that it has a hexagonal lattice structure. The difference is that hBN has electrical insulation properties at different humidity and temperature, which makes it safer and more reliable to regulate and use as an electrolyte membrane in many electrochemical energy conversion and storage systems. In addition, nano-hBN has been proven in PEM due to its advantages such as high specific surface area, high thermal stability, high mechanical strength, excellent proton conductivity and low gas crossover.
[0005] Although functionalized hBN has shown many advantages in PEM, there are also some challenges. The main difficulty of functionalized hBN as an additive is that it is easy to settle when forming a dispersion with electrolytes such as Nafion, and the film brittleness increases, which seriously affects its doping in electrolyte solutions.
[0006] Ionic liquids (ILs) are organic salts composed entirely of cations and anions. Due to their high thermal stability, ionic conductivity, non-volatility and non-flammability, ILs are considered to be "green" media for chemical synthesis, catalytic reactions, as electrolytes for energy converters and energy storage systems, and many other important practical applications. Based on the excellent designability of ILs cations, covalent and non-covalent bonds between ILs and hBN can be constructed to modify hBN to improve the dispersibility and wettability of hBN while reducing the migration of ILs, which broadens the ideas for their application in electrolyte dispersions.
[0007] CN 115181305 A discloses a modified polyimide proton exchange membrane and a preparation method thereof. The ionic liquid is grafted onto the surface of the hexagonal boron nitride by ball milling hexagonal boron nitride and ionic liquid. The introduction of the ionic liquid modified hexagonal boron nitride can significantly enhance the mechanical properties and proton conduction rate of the modified polyimide proton exchange membrane. The ionic liquid grafted hexagonal boron nitride prepared by the method is non-covalently grafted. During the operation of the proton membrane, there is a problem that the ionic liquid is easily lost. However, it does not involve the study of the water absorption rate and anti-oxidation stability of the proton exchange membrane under different temperature conditions.
[0008] CN 108039505 A discloses a two-dimensional boron nitride nanocomposite-based hybrid proton exchange membrane and a preparation method thereof, wherein two-dimensional layered boron nitride is ultrasonically exfoliated in an ethanol phase with the assistance of an ionomer to obtain an ionomer-modified boron nitride nanocomposite, and then the complex is prepared into a dispersion liquid of a certain concentration, and the ionomer-modified two-dimensional boron nitride nanosheet-based composite proton exchange membrane is prepared by suction filtration under pressure, and the composite proton exchange membrane has high proton conductivity and low methanol permeability. The hybrid proton membrane is prepared by suction filtration, and has the problem of poor toughness, and does not involve the water absorption swelling rate and stability research of the proton exchange membrane under different temperature conditions and the coordinated regulation of membrane performance by ionic liquids.
[0009] CN 117107296 A discloses a composite high-temperature proton exchange membrane for water electrolysis and its preparation method and application. Boron nitride is dispersed in a highly polar non-protonic solvent and then mixed with a Nafion solution to obtain a casting solution. The casting solution is cast to obtain a proton exchange membrane. The composite membrane maintains a certain water content under high temperature conditions of 100 to 200°C, thereby avoiding the problem of decreased proton conductivity due to lack of water. The conductivity and tensile strength of the composite membrane are both low, and the research on the antioxidant stability of the proton exchange membrane under different temperature conditions and the coordinated regulation of membrane performance by ionic liquids are not involved.
[0010] CN 114865033 A discloses a composite proton exchange membrane, which includes a matrix and a filler, wherein the matrix includes sulfonated polyetheretherketone, and the filler includes sulfonated ZIF-derived porous carbon material and sulfonated carbon nanotubes. The composite proton exchange membrane prepared by the invention can improve the proton conductivity of the composite proton exchange membrane by filling the sulfonated ZIF-derived porous carbon material and sulfonated carbon nanotubes, and at the same time block the penetration of fuel. By carbonizing the zinc-based ZIF, the disadvantage of its instability in an acidic environment is overcome, making it suitable for preparing the composite proton exchange membrane. However, it does not involve the study of the antioxidant stability of the proton exchange membrane under different temperature conditions and the coordinated regulation of membrane performance by ionic liquids.
[0011] The existing technology has problems such as low mechanical strength of thin PEM, high gas permeability, and poor antioxidant stability. Therefore, how to improve the mechanical strength of the proton exchange membrane while ensuring that the proton exchange membrane has a high proton conduction rate and stability has become a problem that needs to be solved urgently. Summary of the invention
[0012] In order to solve the above technical problems, the purpose of the present invention is to provide an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane and its preparation method and use. The ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane of the present invention can comprehensively improve the proton conductivity, mechanical strength, antioxidant stability and thermal stability of the proton exchange membrane, and at the same time solve the problem that a single ionic liquid doping is easy to lose and a single hexagonal boron nitride doping is easy to settle.
[0013] To achieve this object, the present invention adopts the following technical solutions:
[0014] In a first aspect, the present invention provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, wherein the raw materials for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane include Nafion resin and ionic liquid covalently grafted hexagonal boron nitride;
[0015] In the ionic liquid covalently grafted hexagonal boron nitride, the amine group on the ionic liquid and the epoxy structure on the hexagonal boron nitride modified by the silane coupling agent undergo a ring-opening reaction and are connected in a covalent bond manner.
[0016] The present invention provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane. On the one hand, the ionic liquid has plasticity, proton conductivity and excellent designability. The ionic liquid can improve the flexibility of the polymer matrix and reduce the glass transition temperature (T g ), increase segmented fluidity, and promote the transmission of protons through polymer chains; on the other hand, the introduction of hexagonal boron nitride can improve the mechanical properties and stability of the proton exchange membrane. The uniform dispersion of hexagonal boron nitride nanosheets in the polymer matrix can be improved by covalent grafting with ionic liquids, thereby improving the overall uniformity of the proton exchange membrane and avoiding the problem of unstable membrane performance caused by the leaching of ionic liquids. That is, the covalent grafting of ionic liquids with hexagonal boron nitride can comprehensively improve the proton conductivity, mechanical strength, antioxidant stability, and thermal stability of the proton exchange membrane, while solving the problem of easy loss of single ionic liquid doping and easy sedimentation of single hexagonal boron nitride doping.
[0017] The hexagonal boron nitride in the ionic liquid covalently grafted hexagonal boron nitride of the present invention is in the form of nanosheets. Figure 1 As shown in the figure, the average diameter ranges from 100nm to 200nm. The flaky structure has a larger specific surface area than the spherical structure, which makes it have a larger contact interface with the polymer matrix of Nafion, helps to enhance the interfacial interaction and thus improve the dispersion in the Nafion matrix, and the prepared composite proton exchange membrane is more uniform. In addition, the flaky structure helps to optimize the formation of a more efficient proton conduction channel, while the spherical material may form a discontinuous barrier effect at the interface, thereby reducing the conduction efficiency of the proton. The hydroxylated nano-flaky hexagonal boron nitride can be further grafted with a silane coupling agent, which can act as a chemical bridge between the organic and inorganic phases to achieve covalent bonding of the two phases.
[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0019] Preferably, the average thickness of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane is 50μm-60μm, for example, it can be 50μm, 51μm, 52μm, 53μm, 54μm, 55μm, 56μm, 57μm, 58μm, 59μm or 60μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In a second aspect, the present invention provides a method for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane as described in the first aspect, the preparation method comprising the following steps:
[0021] (1) mixing an ionic liquid, a silane coupling agent-modified hexagonal boron nitride and an alcohol solution, and obtaining the ionic liquid covalently grafted hexagonal boron nitride through a first reaction and a first post-treatment;
[0022] (2) mixing ionic liquid to covalently graft hexagonal boron nitride, Nafion resin and a three-system mixed solvent, and performing a second reaction to obtain a membrane-forming solution;
[0023] (3) Pour the membrane-making solution onto the base membrane, and obtain the proton exchange membrane by scraping and annealing.
[0024] In the present invention, ionic liquid and silane coupling agent are used to modify hexagonal boron nitride to prepare ionic liquid covalently grafted hexagonal boron nitride through reaction. The covalent grafting is more stable and not easy to fall off. The traditional preparation method uses ball milling for mixing, and the ball milling process forms non-covalent grafting. The non-covalent grafting is extremely unstable, and the prepared proton exchange membrane cannot be used for a long time and is very easy to fail. In the present invention, the obtained membrane-making liquid is used to adjust the wet film thickness through scraping, and the prepared proton exchange membrane has uniform thickness, is scientific and reasonable, and is easy to be industrialized.
[0025] Preferably, the ionic liquid in step (2) comprises any one or a combination of at least two of 1-aminopropyl-3-methylimidazolium chloride hydrochloride, 1-aminopropyl-3-methylimidazolium tetrafluoroborate, 1-aminopropyl-3-methylimidazolium hexafluorophosphate, 1-aminopropyl-3-methylimidazolium bistrifluoromethanesulfonyl imide or 1-aminopropyl-3-methylimidazolium nitrate. A typical but non-limiting combination comprises 1-aminopropyl-3-methylimidazolium chloride hydrochloride and 1-aminopropyl A combination of 1-aminopropyl-3-methylimidazolium tetrafluoroborate, a combination of 1-aminopropyl-3-methylimidazolium hexafluorophosphate and 1-aminopropyl-3-methylimidazolium bistrifluoromethanesulfonyl imide, a combination of 1-aminopropyl-3-methylimidazolium bistrifluoromethanesulfonyl imide and 1-aminopropyl-3-methylimidazolium nitrate, a combination of 1-aminopropyl-3-methylimidazolium chloride hydrochloride, 1-aminopropyl-3-methylimidazolium tetrafluoroborate and 1-aminopropyl-3-methylimidazolium hexafluorophosphate.
[0026] The ionic liquid used in the present invention contains an imidazole ring, which has active protons and can form a strong hydrogen bond with a Nafion sulfonic acid group. At the same time, the planar structure of the imidazole ring is conducive to π-π stacking, which helps the ionic liquid to be evenly distributed in the membrane. In addition, the polarity and solubility of the ionic liquid can be adjusted by modifying the substituent of the imidazole ring. The N atom in the imidazole ring is easy to pick up protons at high temperature and can effectively transport protons to adjacent proton receptors to complete proton conduction, thereby improving the electrochemical performance of the composite membrane. If the ionic liquid does not contain an imidazole ring, the reaction with Nafion is weak and there is no π-π stacking effect, which seriously affects its use in the proton exchange membrane.
[0027] Preferably, the concentration of the ionic liquid is 10 mg / mL-15 mg / mL, for example, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL or 15 mg / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the mass ratio of the ionic liquid to the silane coupling agent modified hexagonal boron nitride is 1:(0.5-2), for example, it can be 1:0.5, 1:0.6, 1:0.7, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.6 or 1:2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 1:(0.8-1.2).
[0029] In the present invention, the mass ratio of the reaction ionic liquid to the silane coupling agent modified hexagonal boron nitride is further controlled to be 1:(0.5-2). If the content of the ionic liquid is too much, the hexagonal boron nitride nanosheets will be coated with the ionic liquid, and the strong water absorption of the ions will cause the final proton exchange membrane to swell more and have lower mechanical strength; if the content of the ionic liquid is too little, it is not conducive to the ionic liquid covalently grafted hexagonal boron nitride to provide abundant proton hopping sites, which affects the proton conductivity of the final proton exchange membrane.
[0030] Preferably, the alcohol solution comprises any one of ethylene glycol, isopropanol or hexafluoroisopropanol or a combination of at least two thereof, typical but non-limiting combinations include a combination of ethylene glycol and isopropanol, a combination of isopropanol and hexafluoroisopropanol, a combination of ethylene glycol and hexafluoroisopropanol, and a combination of ethylene glycol, isopropanol and hexafluoroisopropanol.
[0031] Preferably, the temperature of the first reaction is 70°C-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In the present invention, the temperature of the first reaction is further controlled to be 70°C-90°C. The reaction temperature affects the efficiency of the covalent grafting of the ionic liquid. When the reaction is carried out at this temperature, more ionic liquid can be grafted onto the hexagonal boron nitride, thereby improving the efficiency of the reaction. If the reaction temperature is too low, it will be disadvantageous for the ring opening of the epoxy structure of the ionic liquid and the silane coupling agent; if the reaction temperature is too high, the product generated by the ring opening may further react with other reactants, thereby affecting the performance of the composite proton exchange membrane.
[0033] Preferably, the time of the first reaction is 3 h-6 h, for example, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the first post-treatment includes a first solid-liquid separation, a first washing and a first drying performed sequentially.
[0035] Preferably, the first drying temperature is 70°C-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the first drying time is 10 h-20 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the three-system mixed solvent in step (2) comprises a mixture of water, isopropanol and dimethyl sulfoxide.
[0038] The three-system mixed solvent in the present invention has the functions of improving the solubility of Nafion, especially the sulfonic acid group, adjusting the polarity and fluidity of the solvent, improving the uniformity of the coating, and improving the stability of the solution to avoid phase separation or precipitation.
[0039] Preferably, the three-system mixed solvent includes water, isopropanol and dimethyl sulfoxide in a mass ratio of 1:(1-2):(1-2), for example, it can be 1:1:1, 1:1.2:1, 1:1.5:1, 1:1:1.2, 1:1:1.5, 1:1:2 or 1:2:2, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably 1:(1-1.2):(1-1.2).
[0040] Preferably, the ionic liquid covalently grafted hexagonal boron nitride accounts for 1wt%-5wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and Nafion resin, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, preferably 1wt%-3wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In the present invention, the content of ionic liquid covalently grafted hexagonal boron nitride is further optimized to 1wt%-5wt%, so as to further optimize the mechanical properties and electrical properties of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, thereby obtaining an effect of more excellent comprehensive performance, rather than optimizing only one performance. If the content of ionic liquid covalently grafted hexagonal boron nitride is too high, the ionic liquid covalently grafted hexagonal boron nitride will agglomerate in the composite proton exchange membrane, and the agglomeration will lead to the obstruction of the proton conduction channel and the formation of local hard points, thereby reducing the proton conductivity and mechanical properties of the membrane. If the content of ionic liquid covalently grafted hexagonal boron nitride is too low, the performance of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane will not be significantly improved, and the low content may not be sufficient to form a continuous hydrogen bond network or a stable dispersion system, and the proton conductivity or mechanical properties cannot be significantly improved.
[0042] Preferably, the temperature of the second reaction is 60°C-85°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, the time of the second reaction is 10 h-20 h, for example, it can be 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the second reaction process is accompanied by stirring, and the stirring speed is 400rpm-800rpm, for example, it can be 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the second reaction further includes standing for defoaming.
[0046] Preferably, the standing defoaming time is 4h-12h, for example, it can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h or 14h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the solid content of the membrane-forming solution is 15wt%-30wt%, for example, it can be 15wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the base film in step (3) comprises a polyimide film.
[0049] The scraping method of the present invention is: scraping with a scraper of 250 μm-1000 μm.
[0050] Preferably, a second drying step is further performed after the blade coating and before the annealing.
[0051] Preferably, the second drying temperature is 60°C-90°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the second drying time is 10 h-20 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, the annealing temperature is 100°C-150°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In the present invention, annealing is used to release internal stress, optimize proton conduction channels, enhance the mechanical and thermal stability of the membrane and remove residual solvent.
[0055] Preferably, the annealing time is 2 h-8 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, the annealing further includes a second washing step.
[0057] Preferably, the second washing step comprises soaking and washing with hydrogen peroxide solution, sulfuric acid and water.
[0058] Preferably, the average thickness of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane is 50 μm-60 μm.
[0059] Preferably, the silane coupling agent modified hexagonal boron nitride is prepared by the following method, which comprises:
[0060] (a) mixing hexagonal boron nitride, ethanol and alkali solution, performing a first reflux and a third post-treatment to obtain hydroxylated hexagonal boron nitride;
[0061] (b) mixing hydroxylated hexagonal boron nitride and a silane coupling agent solution, and subjecting the mixture to a second reflux and a fourth post-treatment to obtain the silane coupling agent-modified hexagonal boron nitride.
[0062] Preferably, the alkali solution in step (a) comprises sodium hydroxide and / or potassium hydroxide.
[0063] Preferably, the specific steps of mixing hexagonal boron nitride, ethanol and alkali solution in step (a) are: firstly mix hexagonal boron nitride and ethanol, and then add alkali solution after a first ultrasonic dispersion.
[0064] Preferably, the power of the first ultrasonic dispersion is 100W-400W, for example, 100W, 150W, 200W, 250W, 300W, 350W or 400W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] Preferably, the first ultrasonic dispersion time is 0.1h-2h, for example, 0.1h, 0.5h, 1h, 1.3h, 1.5h, 1.8h or 2h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] Preferably, the concentration of hexagonal boron nitride in the mixture of hexagonal boron nitride and ethanol is 4 g / mL-15 g / mL, for example, 4 g / mL, 5 g / mL, 6 g / mL, 7 g / mL, 8 g / mL, 9 g / mL, 10 g / mL, 11 g / mL, 12 g / mL, 13 g / mL, 14 g / mL or 15 g / mL, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0067] Preferably, the concentration of the alkali solution is 3mol / L-5mol / L, for example, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L or 5mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] Preferably, the alkali solution accounts for 10wt%-15wt% of the total mass of hexagonal boron nitride, ethanol and alkali solution, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] Preferably, the temperature of the first reflux is 90°C-110°C, for example, it can be 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] Preferably, the first reflux time is 10h-20h, for example, it can be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] Preferably, the first reflux process is accompanied by stirring, and the stirring speed is 250rpm-450rpm, for example, it can be 250rpm, 300rpm, 350rpm, 400rpm or 450rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] Preferably, the third post-treatment includes a third solid-liquid separation, a third washing and a third drying.
[0073] Preferably, the temperature of the third drying is 70°C-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] Preferably, the third drying time is 10h-20h, for example, it can be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] Preferably, in step (b), the silane coupling agent is pretreated before mixing the hydroxylated hexagonal boron nitride and the silane coupling agent solution, and the pretreatment step comprises: mixing water and ethanol, adding an acid solution to adjust the pH to 2.5-3.5, and adding the silane coupling agent for a third reflux to obtain a silane coupling agent solution.
[0076] Preferably, the temperature of the third reflux is 60°C-90°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] Preferably, the third reflux time is 3h-6h, for example, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] Preferably, the third reflux process is accompanied by stirring, and the stirring speed is 250rpm-450rpm, for example, it can be 250rpm, 300rpm, 350rpm, 400rpm or 450rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] Preferably, the volume fraction of the silane coupling agent solution is 1%-3%, for example, 1%, 1.5%, 2%, 2.5% or 3%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0080] Preferably, the silane coupling agent includes a silane coupling agent containing an epoxy structure.
[0081] Preferably, the silane coupling agent includes any one of 3-glycidoxypropyltrimethoxysilane (GPTMS), 3-glycidoxypropyltriethoxysilane (GPTEOS), glycidoxymethyldimethoxysilane (GMDMS), glycidoxyethyldimethoxysilane (GEDMS), 3-glycidoxypropylmethyldimethoxysilane (GPDMMS), 3-glycidoxypropyldimethylethoxysilane (GPDEOS), glycidoxytrimethylsilane (GTMOS), glycidoxytetraethylorthosilicate (TGS) or glycidoxypropyltriisopropoxysilane (GPTIPS) or a combination of at least two thereof.
[0082] Preferably, the volume ratio of water to ethanol is 1:(3-7), for example, 1:3, 1:4, 1:5, 1:6 or 1:7, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0083] Preferably, the acid solution comprises hydrochloric acid and / or sulfuric acid.
[0084] Preferably, before mixing the hydroxylated hexagonal boron nitride solution and the silane coupling agent solution, the hydroxylated hexagonal boron nitride and ethanol are mixed and ultrasonically dispersed under 300W-500W conditions, for example, 300W, 350W, 400W, 450W or 500W, but not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0085] Preferably, the ultrasonic dispersion time is 20 min-60 min, for example, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0086] Preferably, the mass ratio of the silane coupling agent to the hydroxylated hexagonal boron nitride is 1:(0.5-2.5), for example, 1:0.5, 1:1, 1:1.5, 1:2 or 1:2.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0087] In the present invention, the mass ratio of the silane coupling agent to the hydroxylated hexagonal boron nitride is further optimized to 1:(0.5-2.5), so that more silane coupling agents can be grafted into the hydroxylated hexagonal boron nitride.
[0088] Preferably, the temperature of the second reflux in step (b) is 60°C-90°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0089] Preferably, the second reflux time in step (b) is 3h-6h, for example, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] Preferably, the second reflux process is accompanied by stirring, and the stirring speed is 250rpm-450rpm, for example, it can be 250rpm, 300rpm, 350rpm, 400rpm or 450rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0091] Preferably, the fourth post-treatment includes a fourth solid-liquid separation, a fourth washing and a fourth drying.
[0092] Preferably, the temperature of the fourth drying is 70°C-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] Preferably, the fourth drying time is 10 h-20 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0094] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0095] (I) mixing hexagonal boron nitride and ethanol, performing a first ultrasonic dispersion at 100W-400W for 0.1h-2h to obtain a hexagonal boron nitride solution with a concentration of 4g / mL-15g / mL, adding an alkali solution with a concentration of 3mol / L-5mol / L, performing a first reflux reaction at 250rpm-450rpm and a temperature of 90°C-110°C for 10h-20h, centrifuging and performing a third washing to neutrality, and performing a third drying at 70°C-90°C for 10h-20h to obtain hydroxylated hexagonal boron nitride;
[0096] The hydroxylated hexagonal boron nitride is mixed with ethanol and ultrasonically dispersed for 20 min to 60 min at 300 W to 500 W to obtain a hydroxylated hexagonal boron nitride solution with a concentration of 0.05 g / mL to 0.5 g / mL.
[0097] (II) Mix water and ethanol in a volume ratio of 1:(3-7), add hydrochloric acid and / or sulfuric acid solution to adjust the pH to 2.5-3.5, add 3-glycidyloxypropyltrimethoxysilane (GPTMS), and reflux for a third time at 60°C-90°C for 3h-6h to obtain a silane coupling agent solution with a volume fraction of 1%-3%.
[0098] The hydroxylated hexagonal boron nitride solution and the silane coupling agent solution are mixed in a mass ratio of 1:(0.5-2.5), and a second reflux reaction is carried out at 250rpm-450rpm and a temperature of 90°C-110°C for 3h-6h, vacuum filtration is performed, and the mixture is washed with deionized water and / or ethanol until neutral, and a fourth drying is carried out at 70°C-90°C for 10h-20h to obtain the silane coupling agent modified hexagonal boron nitride.
[0099] (III) Mixing the ionic liquid and the alcohol solution, stirring at 70°C-90°C to completely dissolve the ionic liquid, adding the silane coupling agent modified hexagonal boron nitride according to the mass ratio of ionic liquid to silane coupling agent modified hexagonal boron nitride of 1:(0.8-1.2), first reacting at 70°C-90°C for 3h-6h, centrifuging, washing with ethanol, and first drying at 70°C-90°C for 10h-20h to obtain the ionic liquid covalently grafted hexagonal boron nitride.
[0100] (IV) Mixing ionic liquid covalently grafted hexagonal boron nitride, Nafion resin and a three-system mixed solvent of water, isopropanol and dimethyl sulfoxide in a mass ratio of 1:(1-1.2):(1-1.2), wherein the ionic liquid covalently grafted hexagonal boron nitride accounts for 1wt%-5wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and Nafion resin; carrying out a second reaction at a rotation speed of 400rpm-800rpm and 60℃-85℃ for 10h-20h, standing for 4h-12h for defoaming treatment to obtain a film-making solution; the solid content of the film-making solution is 15wt%-30wt%.
[0101] (V) The membrane-forming liquid is poured onto the base film, and after being coated by scraping, second drying at 60°C-90°C for 10h-20h, and annealing at 100°C-150°C for 2h-8h, a hydrogen peroxide solution, dilute sulfuric acid and water are used for immersion cleaning to obtain an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane with an average thickness of 50μm-60μm.
[0102] In a third aspect, the present invention provides a use of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane as described in the first aspect, wherein the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane is used in a fuel cell or water electrolysis.
[0103] The ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane used for water electrolysis not only has a very high proton conductivity greater than 0.1S / cm, but also has excellent stability, which can reach 0.204S / cm at 80°C, and has broad application prospects in fuel cells and water electrolysis.
[0104] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0105] Compared with the prior art, the present invention has at least the following beneficial effects:
[0106] (1) The present invention provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane. By adding ionic liquid to covalently graft hexagonal boron nitride, on the one hand, the ionic liquid has plasticity, proton conductivity and excellent designability. The ionic liquid can improve the flexibility of the polymer matrix and reduce the glass transition temperature (T g ), increase segmented fluidity, and promote the transmission of protons through polymer chains; on the other hand, the introduction of hexagonal boron nitride can improve the mechanical properties and stability of the proton exchange membrane. The uniform dispersion of hexagonal boron nitride nanosheets in the polymer matrix can be improved by covalent grafting with ionic liquids, thereby improving the overall uniformity of the proton exchange membrane and avoiding the problem of unstable membrane performance caused by the leaching of ionic liquids. That is, the covalent grafting of ionic liquids with hexagonal boron nitride can comprehensively improve the proton conductivity, mechanical strength, antioxidant stability, and thermal stability of the proton exchange membrane, while solving the problem of easy loss of single ionic liquid doping and easy sedimentation of single hexagonal boron nitride doping.
[0107] (2) In the present invention, hexagonal boron nitride is modified by using ionic liquid and silane coupling agent to prepare ionic liquid covalently grafted hexagonal boron nitride through the trans reaction. The covalent grafting is more stable and not easy to fall off. The prepared proton exchange membrane has uniform thickness, is scientific and reasonable, and is easy to industrialize.
[0108] (3) The ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane used for water electrolysis not only has a very high proton conductivity greater than 0.1 S / cm, but also has excellent stability, which can reach 0.204 S / cm at 80°C. It has broad application prospects in fuel cells and water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0109] Figure 1 This is a SEM image of the ionic liquid covalently grafted with hexagonal boron nitride used in the present invention;
[0110] Figure 2 This is a molecular structure diagram of the ionic liquid covalently grafted hexagonal boron nitride prepared in Example 1 of the present invention;
[0111] Figure 3 This is a SEM image of the surface of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane prepared in Example 1 of the present invention;
[0112] Figure 4 is a SEM image of a cross section of an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane prepared in Example 1 of the present invention;
[0113] Figure 5 It is a line graph of the proton conductivity of the proton exchange membranes prepared by Examples 1 to 8 of the present invention and Comparative Examples 1 to 4 at different temperatures;
[0114] Figure 6 1 is a stress-strain curve diagram of the proton exchange membranes prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 4;
[0115] Figure 7 It is a bar graph of water absorption and swelling rate of the proton exchange membranes prepared by Examples 1 to 8 of the present invention and Comparative Examples 1 to 4;
[0116] Figure 8 It is a graph showing the change of mass residual rate of the proton exchange membranes prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 4 over time. DETAILED DESCRIPTION
[0117] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0118] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.
[0119] Example 1
[0120] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, wherein the raw materials for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane include Nafion resin and ionic liquid covalently grafted hexagonal boron nitride;
[0121] The method for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane provided in this embodiment comprises the following steps:
[0122] (I) mixing hexagonal boron nitride and ethanol, performing a first ultrasonic dispersion at 400 W for 10 min to obtain a hexagonal boron nitride solution with a concentration of 8 g / mL, adding a 5 mol / L alkali solution, performing a first reflux reaction at 450 rpm and a temperature of 100° C. for 18 h, centrifuging and performing a third washing to neutrality, and performing a third drying at 80° C. for 12 h to obtain hydroxylated hexagonal boron nitride;
[0123] The hydroxylated hexagonal boron nitride was mixed with ethanol and ultrasonically dispersed at 400W for 20 minutes to obtain a hydroxylated hexagonal boron nitride solution with a concentration of 0.05 g / mL;
[0124] (II) mixing water and ethanol in a volume ratio of 1:5, adding hydrochloric acid solution to adjust the pH to 3, adding 3-glycidyloxypropyltrimethoxysilane (GPTMS), and refluxing for a third time at 60° C. for 3 h to obtain a silane coupling agent solution with a volume fraction of 1% to 3%;
[0125] Mixing a hydroxylated hexagonal boron nitride solution and a silane coupling agent solution in a mass ratio of 1:(0.5-2.5) for 3 h at 400 rpm and 60° C., performing a second reflux reaction, vacuum filtering, washing with deionized water and / or ethanol until neutral, and drying at 80° C. for 12 h to obtain the silane coupling agent-modified hexagonal boron nitride;
[0126] (III) mixing the ionic liquid and the alcohol solution, stirring at 80° C. to completely dissolve the ionic liquid, adding the silane coupling agent modified hexagonal boron nitride according to the mass ratio of the ionic liquid to the silane coupling agent modified hexagonal boron nitride of 1:1, first reacting at 80° C. for 4 h, centrifuging, washing with ethanol, and first drying at 80° C. for 12 h to obtain the ionic liquid covalently grafted hexagonal boron nitride;
[0127] (IV) Mixing ionic liquid covalently grafted hexagonal boron nitride, Nafion resin (Nafion D2020) and a three-system mixed solvent of water, isopropanol and dimethyl sulfoxide in a mass ratio of 1:1:1, wherein the ionic liquid covalently grafted hexagonal boron nitride accounts for 1 wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and the Nafion resin; conducting a second reaction at a rotation speed of 500 rpm and 70°C for 12 hours, standing for 8 hours for defoaming treatment to obtain a film-forming solution; the solid content of the film-forming solution is 16.7 wt%.
[0128] (V) The membrane-forming liquid was poured onto a glass plate with a PI base film, and coated with a 500 μm scraper. The membrane was dried at 80°C for 12 h, annealed at 130°C for 3 h, and then washed with hydrogen peroxide solution, dilute sulfuric acid and water to obtain an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane with an average thickness of 51 μm.
[0129] The molecular structure of the ionic liquid covalently grafted hexagonal boron nitride prepared in step (III) is shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the hydroxylated hexagonal boron nitride is first connected to the silicon in the silane coupling agent and then the epoxy structure of the silane and the side chain amine group of the ionic liquid are opened to finally form the ionic liquid covalently grafted hexagonal boron nitride;
[0130] The SEM images of the prepared ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane surface are as follows: Figure 3 As shown, from Figure 3 It can be seen that the surface of the composite proton exchange membrane covalently grafted with ionic liquid and hexagonal boron nitride is smooth;
[0131] The SEM cross-section of the prepared ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane is as follows: Figure 4 As shown, from Figure 4 It can be seen that the thickness of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane is about 51 μm.
[0132] Example 2
[0133] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, wherein the raw materials for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane include Nafion resin and ionic liquid covalently grafted hexagonal boron nitride;
[0134] The method for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane provided in this embodiment comprises the following steps:
[0135] (I) mixing hexagonal boron nitride and ethanol, performing a first ultrasonic dispersion at 200 W for 1.5 h to obtain a hexagonal boron nitride solution with a concentration of 4 g / mL, adding a 5 mol / L alkali solution, performing a first reflux reaction at 450 rpm and a temperature of 105° C. for 18 h, centrifuging and performing a third washing to neutrality, and performing a third drying at 70° C. for 18 h to obtain hydroxylated hexagonal boron nitride;
[0136] The hydroxylated hexagonal boron nitride was mixed with ethanol and ultrasonically dispersed at 400W for 30 minutes to obtain a hydroxylated hexagonal boron nitride solution with a concentration of 0.1 g / mL;
[0137] (II) mixing water and ethanol in a volume ratio of 1:6, adding hydrochloric acid solution to adjust the pH to 2.5, adding 3-glycidyloxypropyltrimethoxysilane (GPTMS), and refluxing for a third time at 70° C. for 6 hours to obtain a silane coupling agent solution with a volume fraction of 1%;
[0138] Mixing a hydroxylated hexagonal boron nitride solution and a silane coupling agent solution in a mass ratio of 1:1.2, performing a second reflux reaction at 250 rpm and 70° C. for 6 h, vacuum filtering, washing with deionized water and / or ethanol until neutral, and fourth drying at 70° C. for 20 h to obtain the silane coupling agent-modified hexagonal boron nitride;
[0139] (III) mixing the ionic liquid and the alcohol solution, stirring at 70° C. to completely dissolve the ionic liquid, adding the silane coupling agent modified hexagonal boron nitride according to the mass ratio of the ionic liquid to the silane coupling agent modified hexagonal boron nitride of 1:1.2, reacting at 70° C. for 6 h, centrifuging, washing with ethanol, and drying at 70° C. for 20 h to obtain the ionic liquid covalently grafted hexagonal boron nitride;
[0140] (IV) Mixing ionic liquid covalently grafted hexagonal boron nitride, Nafion resin (Nafion D2020) and a three-system mixed solvent of water, isopropanol and dimethyl sulfoxide in a mass ratio of 1:1.2:1.2, wherein the ionic liquid covalently grafted hexagonal boron nitride accounts for 1.5 wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and the Nafion resin; conducting a second reaction at a rotation speed of 400 rpm and 60°C for 20 hours, standing for 4 hours for defoaming treatment to obtain a film-forming solution; the solid content in the film-forming solution is 20 wt%.
[0141] (V) The membrane-forming liquid is poured onto the base film, and after being coated by scraping, second dried at 60° C. for 20 h, and annealed at 100° C. for 6 h, it is washed by immersion in hydrogen peroxide solution, dilute sulfuric acid and water to obtain an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane with an average thickness of 55 μm.
[0142] Example 3
[0143] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, wherein the raw materials for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane include Nafion resin and ionic liquid covalently grafted hexagonal boron nitride;
[0144] The method for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane provided in this embodiment comprises the following steps:
[0145] (I) mixing hexagonal boron nitride and ethanol, performing a first ultrasonic dispersion at 400 W for 0.1 h to obtain a hexagonal boron nitride solution with a concentration of 15 g / mL, adding a 5 mol / L alkali solution, performing a first reflux reaction at 450 rpm and a temperature of 110° C. for 10 h, centrifuging and performing a third washing to neutrality, and performing a third drying at 80° C. for 10 h to obtain hydroxylated hexagonal boron nitride;
[0146] The hydroxylated hexagonal boron nitride was mixed with ethanol and ultrasonically dispersed at 500W for 20 minutes to obtain a hydroxylated hexagonal boron nitride solution with a concentration of 0.5 g / mL;
[0147] (II) mixing water and ethanol in a volume ratio of 1:7, adding sulfuric acid solution to adjust the pH to 3.5, adding 3-glycidyloxypropyltrimethoxysilane (GPTMS), and refluxing for a third time at 110° C. for 3 h to obtain a silane coupling agent solution with a volume fraction of 1% to 3%;
[0148] Mixing a hydroxylated hexagonal boron nitride solution and a silane coupling agent solution in a mass ratio of 1:1, performing a second reflux reaction at 450 rpm and a temperature of 110° C. for 3 h, vacuum filtering, washing with deionized water and / or ethanol until neutral, and fourth drying at 90° C. for 10 h to obtain the silane coupling agent-modified hexagonal boron nitride;
[0149] (III) mixing the ionic liquid and the alcohol solution, stirring at 90° C. to completely dissolve the ionic liquid, adding the silane coupling agent modified hexagonal boron nitride according to the mass ratio of the ionic liquid to the silane coupling agent modified hexagonal boron nitride of 1:1.2, reacting at 90° C. for 3 h, centrifuging, washing with ethanol, and drying at 90° C. for 10 h to obtain the ionic liquid covalently grafted hexagonal boron nitride;
[0150] (IV) Mixing ionic liquid covalently grafted hexagonal boron nitride, Nafion resin (Nafion D2020) and a three-system mixed solvent of water, isopropanol and dimethyl sulfoxide in a mass ratio of 1:0.8:1, wherein the ionic liquid covalently grafted hexagonal boron nitride accounts for 2 wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and the Nafion resin; the second reaction is carried out at a rotation speed of 800 rpm and 85°C for 10 hours, and the film-forming solution is allowed to stand for 12 hours for defoaming treatment to obtain the film-forming solution; the solid content in the film-forming solution is 25 wt%.
[0151] (V) The membrane-forming liquid is poured onto the base film, and after being coated by scraping, second dried at 90° C. for 10 h, and annealed at 150° C. for 2 h, it is washed by immersion in hydrogen peroxide solution, dilute sulfuric acid and water to obtain an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane with an average thickness of 60 μm.
[0152] Example 4
[0153] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, which is different from Example 1 only in that when preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, the ionic liquid covalently grafted hexagonal boron nitride in step (IV) accounts for 0.5wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and Nafion resin.
[0154] Example 5
[0155] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, which is different from Example 1 only in that when preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, the ionic liquid covalently grafted hexagonal boron nitride in step (IV) accounts for 7wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and Nafion resin.
[0156] Example 6
[0157] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, which is different from Embodiment 1 only in that when preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, the temperature of the first reaction in step (III) is 40°C.
[0158] Example 7
[0159] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, which is different from Embodiment 1 only in that when preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, the temperature of the first reaction in step (III) is 110°C.
[0160] Example 8
[0161] This embodiment provides an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, which is different from Example 1 only in that when preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, the ionic liquid used in step (III) is replaced by N,N-dimethylethylammonium-amino methanesulfonate (without an imidazole ring).
[0162] Comparative Example 1
[0163] This comparative example uses a NR212 proton exchange membrane produced by Dupont Company of the United States.
[0164] Comparative Example 2
[0165] This comparative example provides a proton exchange membrane, which is different from Example 1 only in that steps (I), (II) and (III) are not performed when preparing the proton exchange membrane, and no ionic liquid is added to covalently graft hexagonal boron nitride in step (IV).
[0166] Comparative Example 3
[0167] This comparative example provides a hexagonal boron nitride composite proton exchange membrane, which is different from Example 1 only in that when preparing the hexagonal boron nitride composite proton exchange membrane, steps (I), (II) and (III) are not performed, and the hexagonal boron nitride covalently grafted with ionic liquid in step (IV) is replaced by an equal amount of hexagonal boron nitride.
[0168] Comparative Example 4
[0169] This comparative example provides a hexagonal boron nitride composite proton exchange membrane, which is different from Example 1 only in that when preparing the hexagonal boron nitride composite proton exchange membrane, steps (I), (II) and (III) are not performed, and the ionic liquid covalently grafted hexagonal boron nitride in step (IV) is replaced by an equal amount of ionic liquid.
[0170] Test method: The proton exchange membranes prepared in the above examples and comparative examples were tested for proton conductivity, mechanical properties, water absorption, swelling rate and antioxidant rate. The test results are shown in Table 1 below.
[0171] The proton conductivity line graphs of the proton exchange membranes prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 4 at different temperatures are shown in FIG. Figure 5 As shown, from Figure 5It can be seen that the embodiments have increased proton conductivity compared to the comparative example, wherein Example 2 has the best proton conductivity, with a proton conductivity of 0.204 S / cm at 80°C.
[0172] The stress-strain curves of the proton exchange membranes prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 4 are shown in FIG. Figure 6 As shown, from Figure 6 It can be seen that the embodiment has better mechanical properties than the comparative example; as the content of ionic liquid covalently grafted hexagonal boron nitride in PEM increases, the mechanical properties tend to increase first and then decrease.
[0173] The water absorption rate and swelling rate bar graphs of the proton exchange membranes prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 4 are shown in FIG. Figure 7 As shown, from Figure 7 It can be seen that compared with the comparative example, the proton exchange membrane after adding ionic liquid and covalently grafting hexagonal boron nitride in the embodiment maintains a higher water absorption, which is attributed to the effect of the hydrophilic groups in the ionic liquid. At the same time, due to the rigid structure of boron nitride, the composite membrane also has a lower swelling rate.
[0174] The mass residual rate of the proton exchange membranes prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 4 varies with time. Figure 8 As shown, from Figure 8 It can be seen that the examples have a higher mass retention rate after 120h of Fenton test compared with the comparative examples, and Example 2 has the highest mass retention rate, indicating that it has the best antioxidant stability, which is jointly determined by the shielding effect and antioxidant capacity of hBN and the free radical scavenging and dispersing effect of ionic liquids. The synergistic effect of the two forms a physical and chemical dual protection mechanism in the membrane, thereby greatly improving the antioxidant capacity of the proton exchange membrane, which is suitable for use in harsh environments such as water electrolysis and fuel cells.
[0175] Table 1
[0176]
[0177] The test results show that:
[0178] (1) It can be seen from Examples 1 to 3 that the present invention adds ionic liquid to the proton exchange membrane to covalently graft hexagonal boron nitride. The ionic liquid can transport protons to adjacent proton receptors to complete proton conduction, thereby improving the electrochemical performance of the composite membrane; hexagonal boron nitride can improve the mechanical properties and stability of the proton exchange membrane, and the covalent grafting with the ionic liquid can improve the uniform dispersion of the hexagonal boron nitride nanosheets in the polymer matrix, thereby improving the overall uniformity of the proton exchange membrane and avoiding the problem of unstable membrane performance caused by the leaching of the ionic liquid.
[0179] (2) By comparing Example 1 with Example 4-Example 5, it can be seen that the present invention further optimizes the content of ionic liquid covalently grafted hexagonal boron nitride to 1wt%-5wt%, so as to further optimize the mechanical properties and electrical properties of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, thereby obtaining a more excellent comprehensive performance effect, rather than optimizing only one performance. If the content of ionic liquid covalently grafted hexagonal boron nitride is too high, the ionic liquid covalently grafted hexagonal boron nitride will agglomerate in the composite proton exchange membrane, and the agglomeration will lead to the blockage of the proton conduction channel and the formation of local hard points, thereby reducing the proton conductivity and mechanical properties of the membrane; if the content of ionic liquid covalently grafted hexagonal boron nitride is too low, the performance of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane will not be significantly improved, and the low content may not be sufficient to form a continuous hydrogen bond network and a stable dispersion system, and the proton conductivity or mechanical properties cannot be significantly improved.
[0180] (3) By comparing Example 1 with Example 6-Example 7, it can be seen that the present invention further optimizes the temperature of the first reaction to 70°C-90°C. The reaction temperature affects the efficiency of covalent grafting of the ionic liquid. Reacting at this temperature can enable the ionic liquid to be grafted onto hexagonal boron nitride to a greater extent, thereby improving the efficiency of the reaction. If the reaction temperature is too low, the reaction rate will be slowed down, resulting in a long reaction time and reduced production efficiency. If the reaction temperature is too high, it will cause the epoxy structure to decompose or increase side reactions, thereby reducing selectivity.
[0181] (4) By comparing Example 1 with Example 8, it can be seen that the present invention adopts an ionic liquid containing an imidazole ring. The imidazole ring can promote proton conduction through a "proton hopping mechanism" under an electrochemical environment, thereby significantly improving the proton conduction performance of the composite proton exchange membrane. If the ionic liquid does not contain an imidazole ring and cannot form a strong chemical bond or weak interaction (such as a hydrogen bond), the grafting stability and the performance of the composite membrane are seriously affected.
[0182] (5) It can be seen from Example 1 and Comparative Example 1 that the present invention improves the proton conductivity, mechanical strength, antioxidant stability and thermal stability of the proton exchange membrane by adding ionic liquid to covalently graft hexagonal boron nitride into the proton exchange membrane. The technical effect is even better than the performance of the currently commercially available proton exchange membrane of the same thickness.
[0183] (6) It can be seen from Example 1 and Comparative Example 2 that the present invention adds ionic liquid to covalently graft hexagonal boron nitride into the proton exchange membrane. The ionic liquid can transport protons to adjacent proton receptors to complete proton conduction, thereby improving the electrochemical properties of the composite membrane; hexagonal boron nitride can improve the mechanical properties and stability of the proton exchange membrane. By covalently grafting with the ionic liquid, the uniform dispersion of the hexagonal boron nitride nanosheets in the polymer matrix can be improved, the overall uniformity of the proton exchange membrane can be improved, and the problem of unstable membrane performance caused by the leaching of the ionic liquid can be avoided. The addition of ionic liquid covalently grafted hexagonal boron nitride significantly improves the proton conductivity, mechanical strength, antioxidant stability and thermal stability of the proton exchange membrane. When the ionic liquid is not added to covalently graft hexagonal boron nitride, it is difficult to achieve the technical effect of retaining high proton conductivity of the proton exchange membrane while increasing its durability.
[0184] (7) It can be seen from Example 1 and Comparative Examples 3-4 that the uniform dispersion of hexagonal boron nitride nanosheets in the polymer matrix can be improved by covalent grafting with ionic liquids, the overall uniformity of the proton exchange membrane can be improved, and the problem of unstable membrane performance caused by the leaching of ionic liquids can be avoided; when only hexagonal boron nitride is added in Comparative Example 3, the prepared proton exchange membrane has good antioxidant stability, but its proton conductivity is low; it can be seen that the present invention can improve the antioxidant properties of the proton exchange membrane while retaining a high proton conductivity by designing the addition of ILs-hBN. That is, when only hexagonal boron nitride or only ionic liquid is added, it cannot improve the technical effects of the proton conductivity, mechanical strength, antioxidant stability and thermal stability of the proton exchange membrane.
[0185] In summary, the present invention adds ionic liquid to covalently graft hexagonal boron nitride into the proton exchange membrane. The ionic liquid can transport protons to adjacent proton receptors to complete proton conduction, thereby improving the electrochemical performance of the composite membrane; hexagonal boron nitride can improve the mechanical properties and stability of the proton exchange membrane, and the covalent grafting with the ionic liquid can improve the uniform dispersion of the hexagonal boron nitride nanosheets in the polymer matrix, improve the overall uniformity of the proton exchange membrane, and avoid the problem of unstable membrane performance caused by the leaching of the ionic liquid. The addition of the ionic liquid covalently grafted hexagonal boron nitride significantly improves the proton conductivity, mechanical strength, antioxidant stability and thermal stability of the proton exchange membrane.
[0186] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. An ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane, characterized in that: The raw materials for preparing the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane include Nafion resin and ionic liquid covalently grafted hexagonal boron nitride; In the ionic liquid covalently grafted hexagonal boron nitride, the amine group on the ionic liquid and the epoxy structure on the hexagonal boron nitride modified by the silane coupling agent undergo a ring-opening reaction and are connected in a covalent bond manner.
2. The ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane according to claim 1, characterized in that: The average thickness of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane is 50 μm-60 μm.
3. A method for preparing a composite proton exchange membrane of ionic liquid covalently grafted hexagonal boron nitride as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing an ionic liquid, a silane coupling agent-modified hexagonal boron nitride and an alcohol solution, and obtaining the ionic liquid covalently grafted hexagonal boron nitride through a first reaction and a first post-treatment; (2) mixing ionic liquid to covalently graft hexagonal boron nitride, Nafion resin and a three-system mixed solvent, and performing a second reaction to obtain a membrane-forming solution; (3) Pour the membrane-making solution onto the base membrane, and obtain the proton exchange membrane by scraping and annealing.
4. The preparation method according to claim 3, characterized in that: The ionic liquid in step (2) comprises any one of 1-aminopropyl-3-methylimidazolium chloride hydrochloride, 1-aminopropyl-3-methylimidazolium tetrafluoroborate, 1-aminopropyl-3-methylimidazolium hexafluorophosphate, 1-aminopropyl-3-methylimidazolium bistrifluoromethanesulfonyl imide or 1-aminopropyl-3-methylimidazolium nitrate, or a combination of at least two thereof; Preferably, the concentration of the ionic liquid is 10 mg / mL-15 mg / mL; Preferably, the mass ratio of the ionic liquid to the silane coupling agent modified hexagonal boron nitride is 1:(0.5-2), preferably 1:(0.8-1.2); Preferably, the alcohol solution comprises any one of ethylene glycol, isopropanol or hexafluoroisopropanol, or a combination of at least two thereof; Preferably, the temperature of the first reaction is 70°C-90°C, and the time is 3h-6h; Preferably, the first post-treatment comprises a first solid-liquid separation, a first washing and a first drying performed sequentially; Preferably, the first drying is carried out at a temperature of 70°C-90°C and for a time of 10h-20h.
5. The preparation method according to claim 3 or 4, characterized in that: The three-system mixed solvent in step (2) includes a mixture of water, isopropanol and dimethyl sulfoxide; Preferably, the three-system mixed solvent comprises water, isopropanol and dimethyl sulfoxide in a mass ratio of 1:(1-2):(1-2), preferably 1:(1-1.2):(1-1.2); Preferably, the ionic liquid covalently grafted hexagonal boron nitride accounts for 1wt%-5wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and Nafion resin, preferably 1wt%-3wt%; Preferably, the temperature of the second reaction is 60°C-85°C, and the time is 10h-20h; Preferably, the second reaction process is accompanied by stirring, and the stirring speed is 400rpm-800rpm; Preferably, the second reaction further includes standing to defoam; Preferably, the standing defoaming time is 4h-12h; Preferably, the solid content of the membrane-making solution is 15wt%-30wt%.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The base film in step (3) comprises a polyimide film; Preferably, a second drying step is further included after the scraping and before the annealing; Preferably, the second drying temperature is 60°C-90°C and the time is 10h-20h; Preferably, the annealing temperature is 100°C-150°C, and the time is 2h-8h; Preferably, the annealing further includes a second washing step.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The silane coupling agent modified hexagonal boron nitride is prepared by the following method, which comprises: (a) mixing hexagonal boron nitride, ethanol and alkali solution, performing a first reflux and a third post-treatment to obtain hydroxylated hexagonal boron nitride; (b) mixing hydroxylated hexagonal boron nitride and a silane coupling agent solution, and subjecting the mixture to a second reflux and a fourth post-treatment to obtain the silane coupling agent-modified hexagonal boron nitride.
8. The preparation method according to claim 7, characterized in that: The alkali solution in step (a) comprises sodium hydroxide and / or potassium hydroxide; Preferably, the specific steps of mixing hexagonal boron nitride, ethanol and alkali solution in step (a) are: firstly mixing hexagonal boron nitride and ethanol, and then adding alkali solution after first ultrasonic dispersion; Preferably, the power of the first ultrasonic dispersion is 100W-400W, and the time is 0.1h-2h; Preferably, the concentration of hexagonal boron nitride in the mixture of hexagonal boron nitride and ethanol is 4 g / mL-15 g / mL; Preferably, the concentration of the alkali solution is 3mol / L-5mol / L; Preferably, the alkali solution accounts for 10wt%-15wt% of the total mass of hexagonal boron nitride, ethanol and alkali solution; Preferably, the temperature of the first reflux is 90°C-110°C, and the time is 10h-20h; Preferably, the first reflux process is accompanied by stirring, and the stirring speed is 250rpm-450rpm; Preferably, the third post-treatment includes a third solid-liquid separation, a third washing and a third drying; Preferably, the temperature of the third drying is 70°C-90°C and the time is 10h-20h; Preferably, in step (b), the silane coupling agent is pretreated before mixing the hydroxylated hexagonal boron nitride and the silane coupling agent solution, and the pretreatment step comprises: mixing water and ethanol, adding an acid solution to adjust the pH to 2.5-3.5, adding the silane coupling agent for a third reflux to obtain a silane coupling agent solution; Preferably, the temperature of the third reflux is 60°C-90°C, and the time is 3h-6h; Preferably, the third reflux process is accompanied by stirring, and the stirring speed is 250rpm-450rpm; Preferably, the volume fraction of the silane coupling agent solution is 1%-3%; Preferably, the silane coupling agent includes a silane coupling agent containing an epoxy structure; Preferably, the silane coupling agent includes any one of 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, glycidoxymethyldimethoxysilane, glycidoxyethyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyldimethylethoxysilane, glycidoxytrimethylsilane, glycidoxytetraethylorthosilicate or glycidoxypropyltriisopropoxysilane, or a combination of at least two thereof; Preferably, the volume ratio of water to ethanol is 1:(3-7); Preferably, the acid solution comprises hydrochloric acid and / or sulfuric acid; Preferably, before the hydroxylated hexagonal boron nitride solution and the silane coupling agent solution are mixed, the hydroxylated hexagonal boron nitride and ethanol are mixed and ultrasonically dispersed at 300W-500W for 20min-60min to obtain a hydroxylated hexagonal boron nitride solution; Preferably, the mass ratio of the silane coupling agent to the hydroxylated hexagonal boron nitride is 1:(0.5-2.5); Preferably, the temperature of the second reflux in step (b) is 60°C-90°C, and the time is 3h-6h; Preferably, the second reflux process is accompanied by stirring, and the stirring speed is 250rpm-450rpm; Preferably, the fourth post-treatment includes a fourth solid-liquid separation, a fourth washing and a fourth drying; Preferably, the fourth drying is carried out at a temperature of 70° C.-90° C. and for a time of 10 h-20 h.
9. The preparation method according to any one of claims 3 to 8, characterized in that: The preparation method comprises the following steps: (I) mixing hexagonal boron nitride and ethanol, performing a first ultrasonic dispersion at 100W-400W for 0.1h-2h to obtain a hexagonal boron nitride solution with a concentration of 4g / mL-15g / mL, adding an alkali solution with a concentration of 3mol / L-5mol / L, performing a first reflux reaction at 250rpm-450rpm and a temperature of 90°C-110°C for 10h-20h, centrifuging and performing a third washing to neutrality, and performing a third drying at 70°C-90°C for 10h-20h to obtain hydroxylated hexagonal boron nitride; The hydroxylated hexagonal boron nitride and ethanol are mixed and ultrasonically dispersed at 300W-500W for 20min-60min to obtain a hydroxylated hexagonal boron nitride solution with a concentration of 0.05g / mL-0.5g / mL; (II) mixing water and ethanol in a volume ratio of 1:(3-7), adding hydrochloric acid and / or sulfuric acid solution to adjust the pH to 2.5-3.5, adding 3-glycidyloxypropyltrimethoxysilane, and refluxing for a third time at 60° C.-90° C. for 3 h-6 h to obtain a silane coupling agent solution with a volume fraction of 1%-3%; Mixing a hydroxylated hexagonal boron nitride solution and a silane coupling agent solution in a mass ratio of 1:(0.5-2.5) for a second reflux reaction at 250 rpm-450 rpm and a temperature of 90° C.-110° C. for 3 h-6 h, vacuum filtering, washing with deionized water and / or ethanol until neutral, and fourth drying at 70° C.-90° C. for 10 h-20 h to obtain the silane coupling agent modified hexagonal boron nitride; (III) mixing the ionic liquid and the alcohol solution, stirring at 70°C-90°C to completely dissolve the ionic liquid, adding the silane coupling agent modified hexagonal boron nitride according to the mass ratio of the ionic liquid to the silane coupling agent modified hexagonal boron nitride of 1:(0.8-1.2), first reacting at 70°C-90°C for 3h-6h, centrifuging, washing with ethanol, and first drying at 70°C-90°C for 10h-20h to obtain the ionic liquid covalently grafted hexagonal boron nitride; (IV) mixing ionic liquid covalently grafted hexagonal boron nitride, Nafion resin and a three-system mixed solvent of water, isopropanol and dimethyl sulfoxide in a mass ratio of 1:(1-1.2):(1-1.2), wherein the ionic liquid covalently grafted hexagonal boron nitride accounts for 1wt%-5wt% of the total mass of the ionic liquid covalently grafted hexagonal boron nitride and Nafion resin; performing a second reaction at a speed of 400rpm-800rpm and 60℃-85℃ for 10h-20h, standing for 4h-12h for defoaming treatment to obtain a film-making solution; the solid content of the film-making solution is 15wt%-30wt%; (V) The membrane-forming liquid is poured onto the base film, and after being coated by scraping, second drying at 60°C-90°C for 10h-20h, and annealing at 100°C-150°C for 2h-8h, a hydrogen peroxide solution, dilute sulfuric acid and water are used for immersion cleaning to obtain an ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane with an average thickness of 50μm-60μm.
10. Use of the ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane as claimed in claim 1 or 2, characterized in that: The ionic liquid covalently grafted hexagonal boron nitride composite proton exchange membrane is used for fuel cells or water electrolysis.
Citation Information
Patent Citations
Two-dimensional boron nitride nano-composite hybrid proton exchange membrane and preparation method thereof
CN108039505A
Composite proton exchange membrane as well as preparation method and application thereof
CN114865033A
Modified polyimide proton exchange membrane and preparation method thereof
CN115181305A
Composite high-temperature proton exchange membrane for water electrolysis as well as preparation method and application of composite high-temperature proton exchange membrane
CN117107296A